A facile approach for the creation of heteroionic lanthanidomesogens-containing uniform films with enhanced luminescence efficiency. (March 2021) - Knyazev, Andrey A.; Karyakin, Maksim E.; Heinrich, Benoît; Donnio, Bertrand; Galyametdinov, Yuriy G.
Abstract: Adducts of Eu(III), Tb(III), Gd(III) and La(III) tris(β-diketonate) forming mesophases in close temperature ranges were synthesized. The near structural features of these lanthanidomesogens render them suitable for obtaining homogeneous binary mixtures that vitrified on cooling into optically isotropic, self-organizing smectic films over a wide range ratio of the lanthanide complexes. The distribution of the components in the obtained films and their supramolecular organization were studied by polarizing optical microscopy, differential scanning calorimetry, and small-angle X-ray scattering. The mixtures behave as their homologous single components and exhibit smectic A and nematic phases above room temperature, and form anisotropic glasses at room temperature. The dependence of the luminescence on the ratio of each component in the mixtures under investigation has been established and a photoexcitation mechanism proposed. It was shown that the luminescence intensity per mole of the emitting substance in films obtained from mixtures of Eu(III) and Tb(III) complexes increases about three fold when compared with the individual Eu(III) complex. This enhancement of the luminescence was interpreted as the consequence of the very effective intermolecular energy transfer from Tb(III) to Eu(III) complexes, templated by the frozen smectic A supramolecular organization. We thus present here an efficient and facile approach for the creation of novel heteroionic lanthanide-containing high uniaxial materials with effective luminescence and controlled spectral properties. Graphical abstract: Image 1 Highlights: Synthesis of Eu(III), Tb(III) and La(III) tris(β-diketonate) lanthanidomesogens. Homogeneous smectic films of binary mixtures of Eu(III) and Tb(III) complexes. Enhancement of the luminescence by effective intermolecular energy transfer from Tb(III) to Eu(III) complexes.